Gambaran Gaya Hidup Remaja Laki-Laki yang Terpapar Beauty Trend Korea Selatan di Media Sosial - Saputra, Zulian Melentino; Utami, Lusia Savitri Setyo (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2023)
Adolescence is the transition period from childhood and adulthood, beginning at ages 12 and 13 and ending in the teens or early 20s. Today's teenagers have entered a period of having distinctive and modern opinions, preferences, attitudes and behaviors. Recently, teenagers, especially Generation Z, who actively access social media, have been shocked by the popular phenomenon from South Korea or the Korean wave. The researcher aims to know and describe the lifestyle of Generation Z teenagers who are exposed to South Korean beauty trends on social networks. One of the impacts of South Korean beauty trends is the attitude of imitation of everything that is displayed on social media. With this, researchers use modeling theory in accordance with the attitudes of teenagers who are exposed to the impact of this beauty trend. The research approach used by researchers uses a qualitative approach with phenomenological research methods. The result is that all male informants, generation Z, in this study are interested in Korean beauty trends. After being exposed to information on beauty trends by idols on social media, the informants' lifestyles changed drastically from not caring about appearance to caring about beauty. Masa remaja adalah masa transisi dari kanak-kanak dan masa dewasa, dimulai pada usia 12 dan 13 tahun dan berakhir pada remaja atau awal 20-an. Remaja saat ini sudah memasuki masa mempunyai pendapat, preferensi, sikap, dan perilaku yang khas dan modern. Akhir-akhir ini para remaja, khususnya Generasi Z, yang aktif mengakses media sosial, digemparkan dengan fenomena populer dari Negara Korea Selatan atau Korean wave. Peneliti bertujuan mengetahui dan mendeskripsikan gambaran gaya hidup remaja Generasi Z yang terpapar tren kecantikan Korea Selatan di jejaring sosial. Salah satu dampak dari tren kecantikan Korea Selatan adalah sikap peniruan terhadap segala sesuatu yang ditampilkan di media sosial. Dengan ini peneliti memakai teori modeling sesuai dengan sikap para remaja yang terpapar dampak dari tren kecantikan ini. Pendekatan penelitian yang digunakan peneliti menggunakan pendekatan kualitatif, dengan metode penelitian fenomenologi. Hasilnya seluruh informan laki-laki, generasi Z, dalam penelitian ini tertarik dengan tren kecantikan Korea. Setelah terpapar informasi tren kecantikan oleh idola di media sosial, gambaran gaya hidup informan berubah drastis dari yang awalnya tidak peduli dengan penampilan menjadi peduli dengan kecantikan.